Miguel Reale: política e história (1931-1969) - Pinho, Rodrigo Maiolini Rebello (2008)
The objective of this dissertation is to understand the development of the ideas and beliefs of Miguel Reale (1910-2006) from the early 1930s to the late 1960s. Important events in Brazil s history took place in these forty years, in which Reale played a key role as both politician and intellectual. We present his political-ideological trajectory during these decades, which involved his participation in the Brazilian Integralist Action (AIB) party; the Vargas administration; the Progressive Social Party (PSP); and his contribution to the coup d état of 1964. We also examine his notions of history and state in his Integralist and post-Integralist phases. Last of all, we examine how in his pre-1964 writings Reale misrepresents class conflicts by referring to them as social chaos, and how after the coup he calls for revolutionary institutionalization, with the legitimization of political repression and wage cuts. This is, in short, an immanent critique of his writing, in J. Chasin s terms, in an attempt to understand the internal connections that inform his ideological output as a whole